Interethnic differences of cytochrome P450 gene polymorphisms may influence outcome of taxane therapy in Roma and Hungarian populations. Issue 6 (December 2015) - Szalai, Renata; Ganczer, Alma; Magyari, Lili; Matyas, Petra; Bene, Judit; Melegh, Bela
Abstract: Taxanes are widely used microtubule-stabilizing chemotherapeutic agents in the treatment of cancers. Several cytochrome P450 gene variants have been proven to influence taxane metabolism and therapy. The purpose of this work was to determine the distribution of genetic variations of CYP1B1, CYP2C8 and CYP3A5 genes as the first report on taxane metabolizer cytochrome P450 gene polymorphisms in Roma and Hungarian populations. A total of 397 Roma and 412 Hungarian healthy subjects were genotyped for CYP1B1 c.4326C > G, CYP2C8 c.792C > G and CYP3A5 c.6986A > G variant alleles by PCR-RFLP assay and direct sequencing. We found significant differences in the frequencies of homozygous variant genotypes of CYP1B1 4326 GG (p = 0.002) and CYP3A5 6986 GG (p < 0.001) between Roma and Hungarian populations. Regarding minor allele frequencies, for CYP2C8 a significantly increased prevalence was found in 792G allele frequency in the Hungarian population compared to the Roma population (5.83% vs. 2.14%, p = 0.001). Our results can be used as possible predictive factors in population specific treatment algorithms to developing effective programs for a better outcome in patients treated with taxanes.